Pengenalan Zat Aditif dan Adiktif yang Berbahaya Bagi Kesehatan di Lingkungan MTs. Negeri 2 Kabupaten Gorontalo - Herinda Mardin; Hartono D Mamu; Nurul Fajryani Usman; Nur Mustaqimah; Devi Bunga Pagalla (Universitas Negeri Gorontalo, 2022)
The introduction of additives and addictive substances for the younger generation, especially the millennial generation, is very important because children's habits, especially when they are teenagers, do snack activities at school and the surrounding environment without having a selective attitude for the sake of health. The habit of snacking and the lack of knowledge and understanding of healthy snacks and the content of foods that are harmful to health make students not have a selective attitude in consuming snacks in the school environment. Additives contained in food, if excessive can have a negative effect on health. Likewise with addictive substances if misused it will cause negative effects for the body. The purpose of this service activity is to introduce additives and addictive substances that are harmful to health for students aged children and adolescents so that they are able to prevent disease, create a selective attitude in consuming food for the sake of health and save our children from abuse of harmful addictive substances. . The method used in this service activity is the lecture method with a participatory approach through 4 stages of activity, namely, opening, giving material, question and answer/discussion and closing. The socialization activity went well, this could be seen from the enthusiasm of the participants in participating in the socialization activity from beginning to end and actively asking questions and discussing. Learners know the types of additives and addictive substances that are harmful to health and know how to prevent abuse of dangerous addictive substances. In addition, it also adds insight and knowledge to participants about additives and addictive substances that are harmful to health so that students have a selective attitude in snacking activities and consuming food and drinks in the school environment and its surroundings.